Penguatan nilai-nilai gotong royong dalam Masyarakat di Desa Jendi, Kecamatan Selogiri, Kabupaten Wonogiri - Danurwindo, Aryo; Rahayu, Maria Helena Sri; Ciptandriyo, Petrus Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Gotong royong is a characteristic of Indonesian people and has become one of the national identities of Indonesia. However, the gotong royong era experienced a decline due to the growing attitude towards individualism in society. The purpose of this study is to examine how the values ​​of Gotong Royong are reinforced through the communities of Jendi village. This study used a descriptive qualitative research technique by conducting interviews and direct observations. The results of this study indicate that mutual cooperation activities in Jendi village communities can lead to strengthening of values ​​contained in mutual cooperation. These values ​​include the values ​​of togetherness, kinship, mutual aid, sociability, integrity, responsibility, solidarity and togetherness. These values ​​make people realize the importance of mutual cooperation in social life.